EFEKTIFITAS EKSTRAK UMBI GADUNG (Dioscorea hispida) TERHADAP HAMA ULAT GRAYAK (Spodoptera llitura F.) - Yustina Maria Silvia Wonga Puu; Maria Alacok Mana (Agriculture Faculty of Flores University, 2013)
This research aims at revealing the effect of yam extract against Spodoptera litura pest, and some optimum concentration of yam tuber extract which causes the highest mortality of grayak caterpillar pest. The design used in this experiment is Complete Randomized Block Design (CRBD) with treatment used is KO (distilled water), K1, K2, K3, K4. The observation variables in this research are contact poison, a nerve poison, stomach poison, and repellent. The result indicates that yam extract causes mortality in contact poison amounted to 30%, nerve poison amounted to 30%, stomach poison amounted to 30%, and repellent amounted to 23.85%.